Analisis Konseptual Metode Tata Bahasa Terjemah dalam Pengajaran Bahasa Arab di Era Digital - Muhammad Zaidaan; N. Lalah Alawiyah (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2025)
The Grammar Translation Method (MTBT) is a classic approach in Arabic language learning that is still relevant today. This article aims to conceptually analyze the potential development of MTBT in the digital era. This research uses a qualitative approach through a literature study of relevant literature on MTBT and educational technology innovation. The results of the study show that MTBT has great potential to be revitalized through the integration of technologies such as gamification, interactive media, online dictionaries, and artificial intelligence. This integration is able to make MTBT more adaptive, interesting, and support independent and contextual learning. The conclusion of this article emphasizes that MTBT remains important as a foundation for mastering language rules, and its development needs to be directed towards the application of innovative technology-based models. Further empirical research is needed to test the effectiveness of this integrative implementation in various learning contexts.